Actualización de la colección de tipos del herbario MACB, II - Carrasco, María A.; Martín-blanco, Carlos J. (Botanica Complutensis, 2002)
CARRASCO, M. A. & MARTÍN-BLANCO, C. J. 2002. Update of the MACB type collection, II. Bot. Complutensis, 26: 59-62. In this paper the Type collection of the MACB Herbarium is update. We indicate the category of seven names (Holotypus, Isotypus Isolectotypus or Sintypus), as well as the herbariums with other type specimens of the same taxa. The new Typus are: 2 Holotypus, 4 Isotypus, 1 Isolectotypus and 2 Sintypus.
Keywords: Types; Herbarium MACB